Problems with Diagnosis and Management of Pneumonia in SLE Patients: Case Reports - Dharma Putra Wijaya, I Nyoman; Andrika, Putu (Jurnal KESANS : Kesehatan dan Sains, 2024)
Systemic lupus erythematosus (SLE) is a chronic disease with a wide range of manifestations including pulmonary disorders. We reported two cases of patients with SLE and pneumonia. The first patient was a 23-year-old woman who had been diagnosed with SLE and then came with complaints of cough and shortness of breath in the last two weeks. Physical examination found crackles in both lungs. Laboratory examination revealed severe anemia, thrombocytopenia, hyponatremia and hypoalbumin. Thoracic x-ray revealed pneumonia. Patient was diagnosed with pneumonia, relapsed mild SLE, lupus nephritis and severe anemia. She was treated with Levofloxacin 1x750mg, Ceftriaxone 1x2 gram, Methylprednisolone 1x62.5mg and Hydroxychloroquine 1x200mg. The second patient was a 20-year-old woman with complaints of fever, cough, and shortness of breath since two weeks ago. Physical examination showed an increase in RR and temperature. Laboratory examination showed leukopenia, mild anemia, thrombocytopenia and elevated procalcitonin and ESR and hypoalbumin. X-ray examination showed pneumonia. Echocardiography revealed a mild circular pericardial effusion. She was diagnosed with relapsed severe SLE with mild anemia, severe thrombocytopenia and lupus nephritis, pneumonia, hypoalbuminemia, and pericardial effusion. She was treated with Ceftazidime 3x2 grams, Levofloxacin 1x750mg, Hydroxychloroquine 1x200mg, Methylprednisolone 2x62.5mg, TC transfusion 5 bags/day, albumin 20% 100ml and fluconazole 1x200mg was added on fourth day of care. Both patients died on the 10th day. Pulmonary involvement can be primary (caused by SLE itself) or secondary (caused by infection or drug toxicity), acute or chronic. The course, treatment and prognosis vary greatly depending on the specific pattern of the disease.